Incidence of thrombophilia in patients with recurrent pregnancy loss - Bharaswadkar, Ganesh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Approximately 1-3% of women of reproductive age suffer from recurrent pregnancy loss. Objective of this study was to evaluate the association between recurrent pregnancy loss and thrombophilia. Methods: This is a descriptive study, involving retrospective analysis of patients with recurrent pregnancy losses. Patients with recurrent pregnancy loss in whom associated morbidity factors were excluded underwent screening for both acquired and inherited thrombophilia. Results: A total of 20 patients were screened for acquired and inherited thrombophilia with recurrent pregnancy loss. Thrombophilia was diagnosed in 70% cases. Out of which, anticardiolipin antibodies was found positive in 57% of patients, protein C 7% and protein S deficiency was observed in 35% cases. Conclusions: Thrombophilias are associated with recurrent pregnancy loss. Patients in whom other associated morbid factors are excluded, should be offered screening for thrombophilia. Multidisciplinary management involving hematologist is vital for management.